2020
DOI: 10.1016/j.gore.2020.100663
|View full text |Cite
|
Sign up to set email alerts
|

Giant uterine mass with uterine smooth muscle tumor of uncertain malignant potential: A case report

Abstract: Highlights STUMP is a rare disease histologically, and giant STUMP is extremely rare. To our knowledge, present case represents the largest STUMP reported. After successful surgery, the patient is alive without evidence of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…They are diagnosed more frequently in premenopausal women, with an average age of 44 years [ 14 ]. The incidence of these tumors is not very well documented, varying by around 0.01% in patients treated surgically for the presumptive diagnosis of uterine leiomyoma [ 15 ]. In the current research, we observed that the age at diagnosis of patients with this tumor varied between 43 and 48 years, with an average of 45.…”
Section: Discussionmentioning
confidence: 99%
“…They are diagnosed more frequently in premenopausal women, with an average age of 44 years [ 14 ]. The incidence of these tumors is not very well documented, varying by around 0.01% in patients treated surgically for the presumptive diagnosis of uterine leiomyoma [ 15 ]. In the current research, we observed that the age at diagnosis of patients with this tumor varied between 43 and 48 years, with an average of 45.…”
Section: Discussionmentioning
confidence: 99%
“…STUMP tumors are characterized by clinical and histological heterogeneity [ 12 ]. They have a frequency of approximately 0.01%, their prevalence being difficult to assess due to their rarity and variable/subjective diagnostic criteria [ 12 , 13 ]. The incidence of uterine leiomyosarcoma is between 0.35–0.8/100,000, with a prevalence of 3–7/100,000 [ 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can be asymptomatic or present with a wide range of symptoms including heavy menstrual bleeding, fatigue, painful periods, non-cyclic pain, painful intercourse, pelvic pressure, urinary incontinence, constipation, infertility, abortion, and pregnancy complications [4]. Therefore, diagnosis of STUMP is clinically difficult and definite diagnosis can be confirmed after surgery [5].…”
Section: Introductionmentioning
confidence: 99%
“…The term uterine smooth muscle tumor of uncertain malignant potential was firstly used by Kempson in 1973 [1]. World Health Organization (WHO) defines STUMP as intermediate group of uterine smooth muscle tumors which cannot be assigned to either a benign or a malignant tumor, but concern of malignancy remains [5]. Etiology and risk factors of STUMP have not been identified yet.…”
Section: Introductionmentioning
confidence: 99%